PENGARUH MOTIVASI BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR SISWA MPLB DI SMK NEGERI 21 JAKARTA - Nurul Soliha; Dewi Nurmalasari; Ferry Setyadi Atmadja (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Academic achievement is an important indicator of students' learning success and reflects the extent to which learning objectives have been achieved. It is influenced by various internal and external factors, including learning motivation and the peer environment. However, some students still demonstrate suboptimal academic achievement, which is presumed to be associated with low learning motivation and an unsupportive peer environment. Therefore, understanding the influence of these factors is essential for improving students' academic outcomes. This study aims to examine the influence of learning motivation and peer environment on the academic achievement of Grade X and XI Office Management and Business Services students at SMK Negeri 21 Jakarta, both partially and simultaneously. The novelty of this study lies in investigating the combined effects of learning motivation and peer environment on academic achievement by using students' average report card scores as the indicator of academic achievement in the context of vocational high school students. This study employed a quantitative approach with an ex post facto research design. The sample consisted of 103 students selected through proportional random sampling. Data on learning motivation and peer environment were collected using questionnaires, while academic achievement data were obtained from students' average report card scores. The data were analyzed using multiple linear regression with JASP software. The results reveal that learning motivation and peer environment have a positive and significant influence on academic achievement, both partially and simultaneously. The coefficient of determination (R²) of 0.464 indicates that the two independent variables explain 46.4% of the variance in academic achievement, while the remaining 53.6% is influenced by other factors beyond the scope of this study. These findings provide empirical evidence for schools to design strategies that strengthen students' learning motivation and create a supportive peer environment to improve academic achievement.